Utilization of Teak Leaf Extract as a Substitute for Eosin in Hematoxylin Eosin Staining - Agnes Desiana Paa; Agustina W. Djuma; Juliana Christyaningsih (Poltekkes Kemenkes Kupang, 2026)
Hematoxylin–Eosin (HE) staining is widely used in histopathology to visualize tissue morphology. Eosin, a synthetic dye commonly used to stain cytoplasmic components, may cause environmental and health concerns, encouraging the search for safer natural alternatives. Young teak leaves (Tectona grandis) contain anthocyanin pigments with potential as natural staining agents. This study evaluated the effectiveness of teak leaf extract as a substitute for eosin in HE staining of uterine tissue. A quasi-experimental post-test only control group design was applied. Young teak leaves were extracted through maceration using 95% ethanol for seven days, followed by filtration and evaporation to obtain a concentrated extract. Uterine tissue preparations were stained using hematoxylin combined with 75% teak leaf extract, while eosin staining served as the control. Microscopic evaluation at 400x magnification was performed by an anatomical pathology specialist using a staining quality scoring system. The control group stained with eosin demonstrated optimal staining quality, with clear bluish-purple nuclei and bright pink cytoplasm, achieving a good score in all slides. In comparison, teak leaf extract produced pale purple nuclei and brownish-pink cytoplasm that remained distinguishable morphologically, though with lower staining quality. Overall, teak leaf extract demonstrated potential as a natural alternative to eosin, but further optimization is needed to improve staining performance.